Sunflower resistance to multiple downy mildew pathotypes revealed by recognition of conserved effectors of the oomycete Plasmopara halstedii. (7th January 2019) - Pecrix, Yann; Buendia, Luis; Penouilh‐Suzette, Charlotte; Maréchaux, Maude; Legrand, Ludovic; Bouchez, Olivier; Rengel, David; Gouzy, Jérôme; Cottret, Ludovic; Vear, Felicity; Godiard, Laurence
Summary: Over the last 40 years, new sunflower downy mildew isolates ( Plasmopara halstedii ) have overcome major gene resistances in sunflower, requiring the identification of additional and possibly more durable broad‐spectrum resistances. Here, 354 RXLR effectors defined in silico from our new genomic data were classified in a network of 40 connected components sharing conserved protein domains. Among 205 RXLR effector genes encoding conserved proteins in 17 P. halstedii pathotypes of varying virulence, we selected 30 effectors that were expressed during plant infection as potentially essential genes to target broad‐spectrum resistance in sunflower. The transient expression of the 30 core effectors in sunflower and in Nicotiana benthamiana leaves revealed a wide diversity of targeted subcellular compartments, including organelles not so far shown to be targeted by oomycete effectors such as chloroplasts and processing bodies. More than half of the 30 core effectors were able to suppress pattern‐triggered immunity in N. benthamiana, and five of these induced hypersensitive responses (HR) in sunflower broad‐spectrum resistant lines. HR triggered by PhRXLRC01 co‐segregated with Pl22 resistance in F3 populations and both traits localized in 1.7 Mb on chromosome 13 of the sunflower genome. Pl22 resistance was physically mapped on the sunflower genome recently sequenced, unlike all the other downy mildew resistances published so far. PhRXLRC01 and Pl22 are proposed as an avirulence/resistance gene couple not previously described in sunflower. Core effector recognition is a successful strategy to accelerate broad‐spectrum resistance gene identification in complex crop genomes such as sunflower. Significance Statement: Five RXLR‐type effectors of the sunflower downy mildew pathogen conserved in 17 pathotypes of varying virulence, triggered plant immunity in six broad‐spectrum resistant sunflower lines, including two unpublished resistances to all pathotypes. Effector recognition accelerated plant resistance gene identification and fine mapping in complex crop genomes such as sunflower, for which no resistance gene has so far been characterized.